Brenner Base Tunnel exploratory tunnel Ahrental‐Pfons – interaction between tunnel boring machine and rock mass as well as measures to manage fault zones. Issue 5 (1st October 2019) - Flora, Matthias; Grüllich, Sebastian; Töchterle, Andreas; Schierl, Heimo
Abstract: Approx. 42 km of tunnel were excavated on the contract Tulfes‐Pfons H33, including a 15 km long section of the exploratory tunnel, which has been excavated since October 2015 with a gripper TBM from the Ahrental access tunnel southward into the district of Steinach. The interaction of the tunnel boring machine with the rock mass is discussed here as a back analysis of the mechanized tunnelling drive. This article does compare the forecast with the actual geological/geotechnical conditions, but only considers the conditions actually encountered. The back analysis takes place analogously to the principle of geotechnical planning according to the ÖGG (Austrian Society of Geomechanics) guideline, in which, starting from the rock mass structure and the rock mass types, the encountered tunnel face and intrados behaviour are observed and an estimation of the system behaviour is carried out. A description of the tunnelling technology concept completes this paper together with two case studies and the lessons learned. Abstract: Im Baulos Tulfes‐Pfons H33 wurden ca. 42 Tunnelkilometer aufgefahren. Teil davon ist ein 15 km langer Abschnitt des Erkundungsstollens, der seit Oktober 2015 mit einer Gripper‐TBM vom Zufahrtstunnel Ahrental nach Süden bis ins Gemeindegebiet Steinach aufgefahren wurde. Im Sinne einer „back analysis" dieses maschinellen Vortriebs wird die Interaktion der Tunnelbohrmaschine mit dem Gebirge erörtert. In diesem Beitrag wird kein geologisch/geotechnischer Soll‐Ist‐Vergleich durchgeführt, sondern es werden nur die tatsächlich angetroffenen Verhältnisse berücksichtigt. Die „back analysis" erfolgt analog dem Prinzip der geotechnischen Planung gemäß der ÖGG‐Richtlinie für die Phase „Bauausführung", bei der ausgehend vom Gebirgsbau und den Gebirgsarten das angetroffene Ortsbrust‐ und Laibungsverhalten beobachtet und eine Abschätzung des Systemverhaltens durchgeführt werden. Eine Beschreibung des tunnelbautechnischen Konzepts runden zusammen mit zwei Fallbeispielen sowie den daraus gewonnenen Erkenntnissen den Beitrag ab.